Prototheca (Molecular Detection of Human Fungal Pathogens, 2011)
Members of the algae genus Prototheca are the only currently known plants that may cause clinical infections both in humans and animals. The disease patterns caused by protothecae are generally referred to as protothecoses. In 1952, the heterotrophic colorless algae Prototheca (P.) zop¡i was identied as mastitis pathogen for cows for the rst time [1]. Infections were described all over the world and-due to intensive livestock breeding-evolved from an initially sporadic dairy cattle disease into an endemic herd disease. The rare infections of humans are mainly caused by P. wickerhamii; in some cases, P. zop¡i and P. blaschkeae were also isolated. The disease mainly affects immunosuppressed persons, e.g., human immunodeciency virus (HIV) patients. Differentiation is made between cutaneous and subcutaneous protothecoses; in¼ammations of bursae, fascias, and tendon sheaths; and the more rarely occurring systemic protothecosis.